Karya Tari Sang Misionaris : Interpretasi Karya Misi Paulus Tjen On Ngiedi Keuskupan Pangkalpinang - Rully Rochayati; Dewi Purwaningsari (Mahesa Research Center, 2022)
The Missionary is a dance work which is an interpretation of the work of Paulus Tjen On Ngie’s mission in the Pangkalpinang diocese area. The purpose of realizing this dance work is as an expression of his journey in proclaiming the gospel. The purpose of writing is as a from af accountability for the work. In addition, it is necessary to provide knowledge about the background of the work. The process of creating this dance creation methods, namely exploration, improvisasion, giving shape, and evaluation. These stages are combined with observations, interviewer, and documentation to strengthen the process of creating dance work. Related to this method, literature studies and recording in the from of videos or pictures are also carried out during the process is a dance work with a duration of 08.40 minutes. The from of dance work is very completeconsistingof title, dance moves, number of dancer, floor patterns, dance accompaniment mucis, dance properties, make-up, fashion, stage area, lighting.Overall this dance work is formed with a mature and planned concept and is complete according to the needs of the dance itself.